Juvenile Xanthogranuloma: A Case Report and Literature Review of an Underdiagnosed Benign Entity - Paruvathavarthini Thambiraj; Kalaivanan Balasubramanian; Bheemanathi Hanuman Srinivas (International Journal of Advanced Medical and Health Research)
Juvenile xanthogranuloma (JXG) is an uncommon non-Langerhans cell histiocytic lesion that usually occurs at an early age and is asymptomatic. It is usually a self-limiting disorder, and predilection sites are the head and neck, extremities, and trunk. We report a 3-year-old male child who presented to the hospital with asymptomatic swelling in the right upper eyelid region. Excision biopsy was done, and histopathology along with immunohistochemistry was reported as JXG. It is essential to differentiate this condition from childhood malignancy.